2023
DOI: 10.3390/ijms24043871
|View full text |Cite
|
Sign up to set email alerts
|

Dunaliella salina Alga Protects against Myocardial Ischemia/Reperfusion Injury by Attenuating TLR4 Signaling

Abstract: Myocardial ischemia/reperfusion (I/R) injury is marked by rapid increase in inflammation and not only results in myocardial apoptosis but also compromises the myocardial function. Dunaliella salina (D. salina), a halophilic unicellular microalga, has been used as a provitamin A carotenoid supplement and color additive. Several studies have reported that D. salina extract could attenuate lipopolysaccharides-induced inflammatory effects and regulate the virus-induced inflammatory response in macrophages. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Carotenoids are abundant in microalgae [21,22]. These colorful compounds are well known for their antioxidant properties [14,[23][24][25]. They are used as natural colorants [26][27][28] and as food and feed additives or health supplements.…”
Section: Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoids are abundant in microalgae [21,22]. These colorful compounds are well known for their antioxidant properties [14,[23][24][25]. They are used as natural colorants [26][27][28] and as food and feed additives or health supplements.…”
Section: Carotenoidsmentioning
confidence: 99%
“…They are divided into two groups: carotenes and xanthophylls. The former group of compounds are oxygen-free hydrocarbons, such as α-carotene and β-carotene, while the latter compounds are oxygenated derivatives of carotenes (including lutein, violaxanthin, zeaxanthin, fucoxanthin, and astaxanthin) [25,29]. The main sources of carotenoids are microalgae belonging to the Chlorophyceae.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Myocardial inflammation after MIRI exerts a crucial role in aggravating cardiac dysfunction and results in a bad prognosis of myocardial infarction patients. Thus, anti-inflammatory therapy represents a main strategy to attenuate MIRI [25]. AEBP1 is a transcriptional regulator that is implicated in the modulation of various biological processes including inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…A group of rats was subjected to surgical procedures for inducing myocardial I/R injury. D. salina extract treatment (0.1 mg/kg) was able to decrease myocardial infarct size and attenuate the expressions of cyclooxygenase-2 (COX-2) and the activity of STAT1, janus kinase 2 (JAK2), inhibitor of IκB, NF-κB [61]. Yang et al [62] showed that Chlorella pyrenoidosa was able to lower the blood pressure in rats fed a diet containing N ω-nitro-L-arginine methyl ester hydrochloride (L-NAME), which induced endothelial dysfunction (40 mg/kg).…”
Section: Lipids and Other Bioactive Extracts And Moleculesmentioning
confidence: 99%